Developing adaptation outcome indicators to urban heat risks - Tuomimaa, Julia; Käyhkö, Janina; Juhola, Sirkku; Räsänen, Aleksi (Elsevier BV, 2023)
Climate scenarios predict that temperatures will rise and the subsequent heat periods that negatively impact human well-being will increasingly become common. The impact of heat in cities can be adapted to through urban planning, economic investments and other measures. The outcomes of adaptation should be monitored, for example, through indicators. However, adaptation outcome indicators are lacking research and development. We report a co-development process of adaptation outcome indicators that can be used to assess adaptation progress to urban heat risk. We use existing literature, a focus group discussion and a questionnaire to codevelop 16 indicators in the City of Helsinki, Finland. Developed indicators take into account key urban characteristics, including social vulnerability, state of the environment, infrastructure, green–blue infrastructure, economic resources, and knowledge and awareness. This study provides a framework for cities to develop their adaptation monitoring strategy and illustrates a novel empirical case study of derivation process of urban heat risk adaptation indicators.
Keywords: monitoring; adaptation to climate change; indicators; urban heat island; co-development